Relationship of the Phytosterols Intake and Serum Lipids in Patients with Diabetes Type II - A Kooshki (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: In diabetes type II, the prevalence of the hypercholesterol is about 28-34% and hypertriglyseridemia is 5-14%. With regard to the reducing effect of the phytosterols on cholesterol and HDL-C of the serum, this study has been conducted to examine relation of phytosterols intake on serum lipids in type II diabetic patients.METHODS: This cross section study was performed on 200 patients with the Diabetes Type II who referred to the clinic of Diabetes type II in Sabzevar town. After taking written consent from the subjects, questionnaires were completed by an experienced interviewer privately and face to face. The weight as well as their height was measured according to the standardized criteria. Using 24 hour reminder, the essential data on receiving food and feeding frequency was obtained through three consecutive days. Then, the phytosterol content of the food was calculated. Plasma glucose, total cholesterol and triglisride and HDL-C of the serum was determined and formulated through enzymatic calorimetry and LDL-C and then compared.FINDINGS: In this study, mean of BMI of patients were 26.3±1.7 Kg. per sq.m. The average of total cholesterol in group 1 was 263.08±108.52 and in group 2 was 223.02±77.65 mg. per deciliter (p=0.016). The average of LDL-C in group 1 was 168.60±104.78 and in group 2 was 139.21±71.10 mg. per deciliter (p=0.014). LDL-C and HDL-C of the patients’ serum was 151.14±86.67 and 48.58±6.28 mg. per deciliter, respectively. The average dose of the phytosterols in these patients was 376.09±134.43 mg. per day. Phytosterol intake in doses of more than 200 mg. per day with total cholesterol and LDL-C of the diabetic patients type II has a significant inverse correlation.CONCLUSION: The concluding results in this study demonstrate that phytosterol intake in doses of more than 200 mg. per day due to a decrease in total cholesterols and LDL-C of the diabetic patients type II.